Non Compos Mentis: A Meta-Historical Survey of the Historiographic Narratives of Louis Riel's "Insanity" - Betts, Gregory (International Journal of Canadian Studies / Revue internationale d’études canadiennes, 2008)
In light of charges of High Treason, Louis Riel's Defence Counsel pleaded non compos mentis, not guilty by reason of insanity. The prisoner disagreed with his counsel and protested his sanity three times during the trial. With his own lawyers discrediting the validity of his political and religious ambitions, Riel was unsatisfied with his counsel. Similarly, critics, activists, and nationalists also have had an awkward time effectively responding to the question of Riel's insanity. This paper considers the uses of Riel's insanity defense, in particular the opinions of the various psychologists whose judgments determined Riel's fate, his trial, and many of the posthumous responses.